Low-RCS, Circular Polarization, and High-Gain Broadband Antenna Based on Mirror Polarization Conversion Metasurfaces - Liang Zhang; Changqing Liu; Chun Ni; Meng Kong; Xianliang Wu (International Journal of Antennas and Propagation)
In this paper, a novel slot antenna array that is based on mirror polarization conversion metasurfaces (MPCM) is proposed. It achieves circular polarization (CP) and effectively reduces the radar cross section (RCS) and increases gain in the entire x-band. This design uses the mirrored composition of the polarization conversion metasurfaces (PCM) on the top surface of the substrate. The MPCM covers a 2 × 2 slot antenna array that is fed with by a sequentially rotating network. The CP radiation is realized by the polarization conversion characteristics of the PCM. At the same time, the reduction of RCS is achieved by 180° (±30°) reflection phase difference between two adjacent PCMs. The improvement in gain is achieved by using a Fabry–Perot cavity, which is constituted by the ground of the antenna and the PCM. Simulated and measured results show that approximately 46.4% of the operating bandwidth is in the range of 7.5–12 GHz (AR < 3 dB) and the gain of the antenna with MPCM is at least 5 dB higher than the reference antenna. Moreover, the monostatic RCS is reduced from 8 to 20 GHz.